Developing a set of key principles for care planning within older adult care homes: study protocol for a modified Delphi survey - Madalina Toma; Jonathan Taylor; Nick Smith; Sarah Jasim; Jacqueline Damant; Yuri Hamashima; Thais Caprioli (BMJ Open)
Background Older adult care homes in England are required to develop care plans on behalf of each of their residents and to make these documents available to those who provide care. However, there is a lack of formal agreement around the key principles that should inform the development of care plans in care homes for older adults. Using a modified Delphi survey, we intend to generate consensus on a set of key principles that should inform the care planning process.Methods and analysis A two-stage modified Delphi survey will be used to try to reach a consensus on a set of key principles to inform care planning within older adult care homes in England. An interdisciplinary panel of approximately 50 people with experience in care planning will be convened and invited to provide feedback on a set of key principles. We will use an iterative, quasi-anonymous, multistage approach with controlled feedback. In the first round, panellists will be asked to provide feedback on a draft document whose contents have been informed by a systematic scoping review and consultations with care home staff. The first round will be administered and subsequently analysed. The results from the first round will be fed back to the panel members and panellists will be asked to complete a second survey. In each round, panel members will use a 5-point unipolar scale to rate their agreement with the item. Consensus will be considered if ≥75% of participants rate an item as 4–5.Ethics and dissemination This study to which this protocol relates has been granted ethical approval by the University of Kent’s Division for the Study of Law, Society and Social Justice Research Committee Ethics Panel (reference: 1006) on 9 April 2024. The results of this project will be disseminated through conferences and one or more peer-reviewed journals. In a subsequent research phase, the research team plans to share the key principles document developed through this modified Delphi survey with care home residents and their families and friends. We plan to invite their feedback through a series of focus groups with a view to developing a related document for the family and friends of care home residents.